The advantages of elliptic curve cryptography for wireless security. - Lauter, K. (IEEE Wireless communications)
This article provides an overview of elliptic curves and their use in cryptography. The focus is on the performance advantages to be obtained in the wireless environment by using elliptic curve cryptography instead of a traditional cryptosystem like RSA. Specific applications to secure messaging and identity-based encryption are discussed.